Catalyst for preparing glyoxal through ethylene glycol dehydrogenation and application of catalyst

By using a catalyst containing a main catalyst, a co-catalyst and a support in the ethylene glycol dehydrogenation reaction, the problem of low yield of glyoxal preparation in the prior art is solved, and efficient and safe ethylene glycol conversion and glyoxal selectivity are achieved, and production efficiency and product quality are improved.

CN119500152APending Publication Date: 2025-02-25XINNUO CHEM TECH (TAIXING) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411623534.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, the yield of ethylene glycol dehydrogenation to prepare glyoxal is relatively low, and there are problems of poor product quality, high overall energy consumption and many side reactions.

Method used

A catalyst is used, which includes 45-55% main catalyst, 25-35% cocatalyst and 10-30% support. The main catalyst and cocatalyst are reduced and the support precursor are uniformly dispersed with the main and cocatalysts to form a uniformly dispersed dispersed phase, avoiding the enrichment of main and cocatalysts and improving the dehydrogenation reaction efficiency of ethylene glycol.

Benefits of technology

At lower reaction pressure and temperature, the catalyst can effectively improve the conversion rate of ethylene glycol and the selectivity of glyoxal. The conversion rate of ethylene glycol remains above 97.5%, the selectivity of glyoxal remains above 97.2%, and the yield of ethylene glycol remains above 94.9%, and the reaction is safe, simple and cost-effective.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a catalyst for preparing glyoxal from ethylene glycol. The catalyst comprises the following components in percentage by weight: 45-55% of a main catalyst, 25-35% of a cocatalyst and 10-30% of a carrier, wherein the main catalyst is at least one metal of IB and VIII or an oxide thereof; the cocatalyst is at least one metal of IIB and VIB or an oxide thereof; the carrier is at least one of aluminum oxide and silicon oxide; before the catalyst is used, the catalyst is reduced firstly, and oxides contained in the main catalyst and the cocatalyst are reduced into metal elementary substances. The invention also discloses an application of the catalyst in preparation of glyoxal through ethylene glycol dehydrogenation. The aluminum source and the silicon source in the carrier precursor are colloidal, part of the main catalyst and the auxiliary catalyst are exposed on the surface of the carrier pore channel, the main catalyst and the auxiliary catalyst form a uniformly dispersed dispersion phase, the aggregation phenomenon does not exist, the dehydrogenation reaction of ethylene glycol can be mild, and the conversion rate and the selectivity of glyoxal can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a catalyst for preparing glyoxal by dehydrogenating ethylene glycol and application of the catalyst in preparing glyoxal by dehydrogenating ethylene glycol. Background Art

[0002] Glyoxal is an important organic compound with the molecular formula C2H2O2. It is a colorless or yellow deliquescent crystal or liquid. Its vapor is green. It is soluble in ethanol, ether, water, etc. It has active chemical properties and can react with ammonia, amides, aldehydes, and carboxyl-containing compounds by addition or condensation. Traditional methods for synthesizing glyoxal include ethylene oxide, ethylene glycol gas phase oxidation, acetaldehyde nitric acid oxidation, carbonylation reaction, etc. Among them, ethylene glycol gas phase oxidation and acetaldehyde nitric acid oxidation are the main industrial production methods.

[0003] In the prior art, silver is usually used as the main catalyst, and phosphorus, copper, etc. are used as auxiliary catalysts. For example, in the patent with the authorization announcement number CN101024183B, a copper-loaded crystalline silver catalyst for gas-phase oxidation synthesis of glyoxal and a preparation method thereof are disclosed. The catalyst is obtained by chemically depositing a modified amount of copper on crystalline silver particles, and the copper loading is 1-100 mg / g. The chemical plating solution is composed of copper ammonia complex ions, ammonia water and a reducing agent. The crystalline silver particles are placed in the plating solution for chemical plating, and then filtered and roasted to obtain the catalyst.

[0004] Patent CN109678683A discloses a process for preparing glyoxal, wherein ethylene glycol is preheated and gasified, mixed with air and inert gas and then enters a catalytic reactor, the reaction temperature is 600-605°C, and the pressure is 0.74MPa, the reaction product is chilled with water to 200-230°C, and then sent to an absorption tower for repeated absorption to obtain a finished product; wherein the catalyst active ingredients in the catalytic reactor are composed of silver, phosphorus and silicon, and the mass proportions are 99.2%, 0.3% and 0.5% respectively. The present invention has high production efficiency and a glyoxal yield of up to 85%.

[0005] Zhang Zhiyong et al. mentioned in "Research Progress on Glyoxal Preparation Technology" that the traditional catalyst is a phosphor-copper catalyst, which is a phosphor-copper alloy containing 2.3% phosphorus, and the mass yield of glyoxal is more than 50%.

[0006] Patent CN116689003A discloses a catalyst for preparing glyoxal from ethylene glycol, wherein the raw materials include, by weight: 45-55 parts of a porous carrier, 8.2-9.5 parts of copper phosphate, 7.5-8 parts of silver phosphate, 0.5-1 parts of selenium dioxide, and 100 parts of hydrofluoric acid, wherein the mass fraction of hydrogen fluoride in the hydrofluoric acid is 5.2-7.5%. The reaction temperature is lower than 500°C, the conversion rate of glyoxal is higher than 95%, and the selectivity is higher than 85%.

[0007] Ma Xiaoli et al. mentioned a gas-phase catalytic oxidation method of ethylene glycol in "Comparison of Energy-saving Processes for the Preparation of Glyoxal by Catalytic Oxidation of Ethylene Glycol", which is to preheat and gasify ethylene glycol, mix it with circulating gas and enter the catalytic reactor, react at 650℃-670℃, and the product is quenched with water to form a glyoxal aqueous solution, and then undergo subsequent treatment processes such as decolorization and vacuum filtration to obtain the glyoxal product. The single-pass conversion rate of ethylene glycol is 80%-85%, and the glyoxal concentration of the product is generally 30%-40%. The acetaldehyde nitric acid oxidation method uses copper nitrate as a catalyst and nitric acid for liquid-phase oxidation. The general yield of glyoxal is about 32%-40%.

[0008] The disadvantage of the ethylene glycol gas phase catalytic oxidation method is that the product quality is poor and contains a certain amount of formaldehyde, alcohol, and acid substances, which need further purification. The ethylene glycol catalytic oxidation process has the disadvantages of high comprehensive energy consumption, poor product quality, and low oxidation reaction conversion rate. The disadvantage of the acetaldehyde nitric acid oxidation method is that there are many side reactions. The most important side reaction is that part of the acetaldehyde is oxidized to acetic acid, and a small amount of the target product glyoxal is further oxidized to glyoxylic acid and oxalic acid. The purification of the crude product is relatively difficult. In addition, there are also disadvantages such as serious corrosion of production equipment and more three wastes.

[0009] In view of the above problems in the prior art, further research is still needed to improve the yield of preparing glyoxal from ethylene glycol. Summary of the invention

[0010] In order to solve the problem of low yield of preparing glyoxal by dehydrogenation of ethylene glycol in the prior art, the present application proposes a catalyst for preparing glyoxal from ethylene glycol, which comprises the following components in weight ratio:

[0011] 45-55% of the main catalyst, 25-35% of the co-catalyst, and 10-30% of the carrier; wherein: the main catalyst is at least one metal selected from IB and VIII or its oxide; the co-catalyst is at least one metal selected from IIB and VIB or its oxide; the carrier is at least one of aluminum oxide and silicon oxide; when calculating the ratio of the main catalyst to the co-catalyst, both are converted to metal elements for calculation;

[0012] Before using the catalyst, the catalyst is first reduced to reduce the oxides contained in the main catalyst and the co-catalyst to metal elements.

[0013] Preferably, the main catalyst is at least one of copper, copper oxide, iron and iron oxide; the co-catalyst is at least one of zinc, zinc oxide, cadmium, cadmium oxide, molybdenum and molybdenum oxide. The aluminum source is pseudo-boehmite, SB powder, aluminum oxide dry gel, aluminum nitrate, etc., and the silicon source is white carbon black, silica sol, etc.

[0014] Further, the catalyst is prepared by the following steps:

[0015] (1) Prepare the soluble salts of the main catalyst and the co-catalyst into an aqueous solution, stir evenly, and then add the carrier precursor to the aqueous solution to form a reaction solution:

[0016] (2) maintaining stirring, heating the reaction solution to a set temperature, adding an alkaline precipitant, performing a precipitation reaction, aging, and then filtering to obtain a filtrate;

[0017] (3) The filtered material is dried, calcined, and pressed into tablets to form a product.

[0018] The carrier precursor is at least one of an aluminum source and a silicon source, wherein the aluminum source is pseudo-boehmite, SB powder, aluminum oxide dry gel or aluminum nitrate, etc., and the silicon source is white carbon black or silica sol, etc., wherein the white carbon black is preferably fumed white carbon black. The alkaline precipitant is ammonia water, sodium carbonate solution, ammonium bicarbonate solution, etc.

[0019] In the present application, the carrier precursor reacts with the soluble salt of the main and co-catalysts, and the carrier precursor can be evenly dispersed in the carrier during the process of forming the carrier, so as to avoid the main and co-catalysts from being enriched in some areas. When the main and co-catalysts are enriched, the side reactions of ethylene glycol in the dehydrogenation process will increase, and the selectivity of glyoxal will be reduced. When nano-alumina and silicon oxide are directly used as carriers to adsorb the main and co-catalysts, the pores of the carrier will form an aggregation area of ​​catalyst particles, resulting in the enrichment of the main and co-catalysts.

[0020] In the present application, the aluminum source and silicon source in the carrier precursor are both in colloidal form. After precipitation, they form an inclusion body with the main and auxiliary catalysts. In the subsequent calcination process, part of the main and auxiliary catalysts will be exposed on the surface of the carrier pores. The main and auxiliary catalysts form a uniformly dispersed dispersed phase without aggregation, which can make the dehydrogenation reaction of ethylene glycol relatively mild, which is beneficial to improve the conversion rate and selectivity of glyoxal.

[0021] The specific surface area of ​​the catalyst prepared in this application is 150-200m 2 / g. The catalyst can catalyze ethylene glycol at a relatively low reaction pressure and reaction temperature to dehydrogenate it into glyoxal. Compared with the existing ethylene glycol oxidation process for glyoxal, the catalyst has higher safety, simple operation and low cost. Using the catalyst in the present application, the ethylene glycol conversion rate is maintained at more than 97.5%, the glyoxal selectivity can be maintained at more than 97.2%, and the ethylene glycol yield is maintained at more than 94.9%. The reaction temperature is safer, simpler, and less expensive than the ethylene glycol gas phase oxidation process, and is more feasible.

[0022] Specifically, to ensure uniform dispersion and uniform dispersion with the carrier precursor, the mass percentage of the soluble salt of the main catalyst is 5-16%, and the mass percentage of the soluble salt of the co-catalyst is 4-8% in the aqueous solution. When the concentration of the soluble salt of the main catalyst or the co-catalyst is too high, the main catalyst and the co-catalyst will be aggregated on the carrier, resulting in a point with strong local activity. When used as a catalyst, it is easy to cause side reactions and reduce the yield of glyoxal. When the concentration of the soluble salt of the main catalyst or the co-catalyst is too low, it has no great effect on the quality of the catalyst, mainly because the preparation cost of the catalyst is increased, and the production efficiency of the catalyst is reduced.

[0023] Specifically, to ensure the smooth progress of the reaction, in step (2), the precipitation temperature is 50-90°C, the pH value during the precipitation reaction is 8-11, and the aging time is 2-12h. The precipitation temperature is more preferably 60-80°C; the pH value during the precipitation reaction is preferably 9-10; and the aging time is more preferably 3-8h. A precipitation temperature higher than 95°C will cause the mixed solution to boil and will also affect the specific surface area of ​​the catalyst, making the specific surface area greater than 200m 2 / g. If the precipitation temperature is too low, the precipitation will be incomplete, which will make the catalyst effect poor. If the pH value is higher than 11, it will cause waste of reagents, increase costs, and corrode equipment. If the pH value is lower than 9, the precipitation will be incomplete. The precipitation pH value of zinc ions is about 8.04. If the aging time is too short, the catalyst precipitation will be incomplete.

[0024] Specifically, in step (3), the drying temperature is 90-150° C., and the drying time is 0.5-5 h; the roasting temperature is 500-600° C., and the roasting time is 3-5 h.

[0025] At the above temperature, the aluminum oxide (Al2O3) formed is a transitional state of γ-Al2O3, which is a fine grain of 5-10nm and has a large specific surface area. It has the advantages of good adsorption function and high chemical reaction activity. The catalyst formed by it as a carrier can allow ethylene glycol to enter its pores during the dehydrogenation reaction of ethylene glycol. Under the action of the main and auxiliary catalyst components, the hydrogen carried by ethylene glycol is stripped. When the calcination temperature is too high, the crystal form of aluminum oxide gradually changes to δ-Al2O3, accompanied by volume shrinkage and pore narrowing, resulting in reduced adsorption function and increased difficulty for ethylene glycol to enter its pores. The catalytic effect of the catalyst is mainly manifested on the surface of the catalyst.

[0026] When the calcination temperature is too low, the crystal form of alumina is mainly η-Al2O3. Although it has a pore volume and specific surface area similar to γ-Al2O3, its surface acidity is too high, which will cause the generated glyoxal to react with ethylene glycol to condense, resulting in an increase in side reactions.

[0027] If the drying temperature is too low, the moisture in the catalyst cannot be effectively removed. If the roasting time is too long and the temperature is too high, the catalyst may coke and aggregate, and the catalyst components may change. The aggregation of the catalyst may make the copper particles larger, thus affecting the activity of the catalyst. High temperature may also bring certain safety hazards.

[0028] Secondly, the present application also discloses the use of any of the above-mentioned catalysts in the dehydrogenation of ethylene glycol to produce glyoxal.

[0029] Specifically, when the catalyst is used to dehydrogenate ethylene glycol to prepare glyoxal, the catalyst is first crushed into particles of 20-40 mesh and loaded into a reactor, and the catalyst is reduced at a pressure of 1.8-2.2 MPa and a temperature of 200° C.-300° C.; then ethylene glycol is introduced into the reactor for a dehydrogenation reaction; during the dehydrogenation reaction, the reaction pressure is normal pressure, the reaction temperature is 350-380° C., and the mass space velocity is 0.1-0.4 h -1 Specifically, the reactor is a fixed bed reactor. During the reaction, the generated hydrogen is discharged from the reactor along with the reaction mixture and then separated and recovered.

[0030] Before ethylene glycol is introduced into the reactor, hydrogen is first introduced into the reactor to reduce the main catalyst oxide and the co-catalyst oxide in the catalyst to elemental metals to ensure the activity of the catalyst. In this application, normal pressure reaction and low temperature reaction are adopted to reduce the severity of the reaction, reduce the generation of side reactions, improve the selectivity of glyoxal, and reduce the energy consumption of the reaction. Under the above reaction conditions, ethylene glycol can be smoothly converted into glyoxal, wherein the ethylene glycol conversion rate is maintained at more than 97.5%, the glyoxal selectivity can be maintained at more than 97.2%, and the yield of ethylene glycol is maintained at more than 94.9%. DETAILED DESCRIPTION

[0031] In the following examples, the proportions of the components in the catalyst are all weight percentages, and the proportions of the main catalyst and the co-catalyst are all converted into metal elements.

[0032] Example 1

[0033] Add 46.89g of copper nitrate and 27.71g of zinc nitrate to 500g of distilled water, then add 6.35g of pseudo-boehmite, stir evenly, heat to 70°C, drop 20% sodium carbonate solution to the solution until pH is 9, keep the temperature at 70°C, and perform precipitation reaction. After the reaction is completed, age for 6h, filter, wash the filtrate with distilled water, dry at 120°C for 2h, and then roast at 550°C for 4h, press into tablets, and the catalyst is numbered 1#. Catalyst 1# contains 50% Cu, 30% Zn, and 20% alumina. The weight of the pseudo-boehmite is calculated as alumina.

[0034] Example 2

[0035] Add 60.50g of ferric nitrate and 24.42g of zinc nitrate to 500g of distilled water, then add 5.60g of pseudo-boehmite, stir evenly, heat to 60°C, drop 20% sodium carbonate solution to the solution until pH is 9, keep the temperature at 60°C, and perform precipitation reaction. After the reaction is completed, age for 4h, filter, wash the filtrate with distilled water, dry at 120°C for 2h, and then roast at 500°C for 4h, press into tablets, and the catalyst number is 2#, and the 2# catalyst contains 50% Fe, 30% Zn, and 20% alumina. The weight of the pseudo-boehmite is calculated as alumina.

[0036] Example 3

[0037] Add 23.44g of copper nitrate, 34.31g of iron nitrate and 27.71g of zinc nitrate to 400g of distilled water, then add 6.35g of pseudo-boehmite, stir evenly, heat to 80°C, drop 20% sodium carbonate solution by weight to the solution until the pH is 9, keep the temperature at 80°C, and perform precipitation reaction. After the reaction is completed, age for 12h, filter, wash the filtrate with distilled water, dry at 120°C for 2h, and then roast at 600°C for 3h, press into tablets, and the catalyst number is 3#. The 3# catalyst contains 25% Cu, 25% Fe, 30% Zn, and 20% alumina. The weight of the pseudo-boehmite is calculated as alumina.

[0038] Example 4

[0039] Add 46.89g of copper nitrate, 18.46g of zinc nitrate and 6.7g of cadmium nitrate to 250g of distilled water, then add 6.35g of pseudo-boehmite, stir evenly, heat to 90°C, drop 20% sodium carbonate solution to the solution until pH is 9, keep the temperature at 90°C, and perform precipitation reaction. After the reaction is completed, age for 10h, filter, wash the filtrate with distilled water, dry at 120°C for 2h, and then roast at 500°C for 5h, press into tablets, and the catalyst number is 4#. Catalyst 4# contains 50% Cu, 20% Zn, 10% Cd, and 20% alumina. The weight of the pseudo-boehmite is calculated as alumina.

[0040] Example 5

[0041] Add 37.50g of copper nitrate and 27.71g of zinc nitrate to 300g of distilled water, then add 9.53g of pseudo-boehmite, stir evenly, heat to 70°C, drop 20% sodium carbonate solution to the solution until pH is 8, keep the temperature at 70°C, and perform precipitation reaction. After the reaction is completed, age for 6h, filter, wash the filtrate with distilled water, dry at 90°C for 2h, and then roast at 550°C for 4h, press into tablets, and the catalyst number is 5#. The 5# catalyst contains 40% Cu, 30% Zn, and 30% alumina. The weight of the pseudo-boehmite is calculated as alumina.

[0042] Example 6

[0043] Add 56.25g of copper nitrate and 27.71g of zinc nitrate to 300g of distilled water, then add 3.18g of pseudo-boehmite, stir evenly, heat to 70°C, drop 20% sodium carbonate solution to the solution until the pH is 10, keep the temperature at 70°C, and perform precipitation reaction. After the reaction is completed, age for 6h, filter, wash the filtrate with distilled water, dry at 150°C for 2h, and then roast at 550°C for 4h, press into tablets, and the catalyst number is 6#. The 6# catalyst contains 60% Cu, 30% Zn, and 10% alumina. The weight of the pseudo-boehmite is calculated as alumina.

[0044] Example 7

[0045] Add 46.89g of copper nitrate and 18.46g of zinc nitrate to 350g of distilled water, then add 9.53g of pseudo-boehmite, stir evenly, heat to 70°C, drop 20% sodium carbonate solution to the solution until the pH is 11, keep the temperature at 70°C, and perform precipitation reaction. After the reaction is completed, age for 6h, filter, wash the filtrate with distilled water, dry at 90°C for 5h, and then roast at 550°C for 4h, press into tablets, and the catalyst number is 7#. Catalyst 7# contains 50% Cu, 20% Zn, and 30% alumina. The weight of the pseudo-boehmite is converted to alumina.

[0046] Example 8

[0047] Add 46.89g of copper nitrate and 36.93g of zinc nitrate to 750g of distilled water, then add 3.18g of pseudo-boehmite, stir evenly, heat to 70°C, drop 20% sodium carbonate solution to the solution until pH is 9, keep the temperature at 70°C, and perform precipitation reaction. After the reaction is completed, age for 6h, filter, wash the filtrate with distilled water, dry at 150°C for 1h, and then roast at 550°C for 4h, press into tablets, and the catalyst number is 8#, which contains 50% Cu, 40% Zn, and 10% alumina. The weight of the pseudo-boehmite is calculated as alumina.

[0048] Example 9

[0049] Add 46.89g of copper nitrate and 27.71g of zinc nitrate to 450g of distilled water, then add 6.35g of silica sol, stir evenly, heat to 70°C, drop 20% sodium carbonate solution to the solution until pH is 9, keep the temperature at 70°C, and perform precipitation reaction. After the reaction is completed, age for 6h, filter, wash the filtrate with distilled water, dry at 100°C for 3h, and then roast at 550°C for 4h, press into tablets, and the catalyst number is 9#, and the 9# catalyst contains 50% Cu, 30% Zn, and 20% alumina. The weight of the silica sol is calculated as silicon oxide.

[0050] Comparative Example 1

[0051] Add 46.89g of copper nitrate and 27.71g of zinc nitrate to 500g of distilled water, then add 6.35g of aluminum oxide, stir evenly, heat to 70°C, add 20% sodium carbonate solution by weight to the solution until the pH is 9, maintain the temperature at 70°C, and carry out precipitation reaction. After the reaction is completed, age for 6h, filter, wash the filtrate with distilled water, dry at 120°C for 2h, and then roast at 550°C for 4h, press into tablets, and the catalyst is numbered 10#.

[0052] The preparation method of alumina in this comparative example is as follows: pseudo-boehmite is calcined at 550°C for 4 hours and then ground to form a carrier.

[0053] Comparative Example 2

[0054] This comparative example is substantially the same as Example 1, except that the amount of pseudo-boehmite added is 13.97 g, calculated as alumina. Catalyst No. 11#.

[0055] Comparative Example 3

[0056] This comparative example is substantially the same as Example 1, except that the amount of pseudo-boehmite added is 2.2 g, calculated as alumina. Catalyst No. 12#.

[0057] Comparative Example 4

[0058] This comparative example is basically the same as Example 1, except that the amount of distilled water added is 150 g. Catalyst No. 13#.

[0059] Comparative Example 5

[0060] This comparative example is basically the same as Example 1, except that the temperature is maintained at 100° C. during the precipitation reaction. Catalyst No. 14#.

[0061] Comparative Example 6

[0062] This comparative example is basically the same as Example 1, except that in step (3), the calcination temperature is 720° C. Catalyst No. 15#.

[0063] Comparative Example 7

[0064] This comparative example is basically the same as Example 1, except that in step (3), the calcination temperature is 400° C. Catalyst No. 16#.

[0065] Comparative Example 8

[0066] This comparative example is basically the same as Example 1, except that in step (3), the calcination time is 7 hours. Catalyst No. 17#.

[0067] The catalysts prepared in the examples and comparative examples were crushed into 20-40 powders, and then loaded into a 30 ml fixed bed reactor. Hydrogen was introduced at 2.0 MPa and 250° C. to reduce the catalyst for 5 hours. The pressure of the reactor was then reduced to normal pressure, and ethylene glycol raw material was introduced for dehydrogenation reaction. The reaction conditions were: temperature: 360° C., pressure: normal pressure, space velocity 0.2 h -1 , the ratio of hydrogen to ethylene glycol is 30:1. The data obtained are listed in Tables 1 and 2:

[0068] Table 1 Catalytic effects of the catalysts prepared in Examples 1-9:

[0069] Catalyst name 1# 2# 3# 4# 5# 6# 7# 8# 9# <![CDATA[Specific surface area m 2 / g]]> 173 195 188 151 180 197 185 163 169 Ethylene glycol conversion % 99.6 98.3 97.5 98.7 98.3 98.5 99.1 99.3 98.2 Glyoxal selectivity % 98.7 97.2 97.3 97.3 98.2 97.6 97.8 97.9 97.5 Glyoxal yield% 98.3 95.5 94.9 96.0 96.5 96.1 96.9 97.2 95.7

[0070] Table 2 Catalytic effects of the catalysts prepared in Comparative Examples 1-8:

[0071] Catalyst name 10# 11# 12# 13# 14# 15# 16# 17# <![CDATA[Specific surface area m 2 / g]]> 178 185 122 162 265 121 172 155 Ethylene glycol conversion % 99.5 92.6 97.8 99.1 98.9 80.6 96.1 99.0 Glyoxal selectivity % 92.3 97.8 93.3 91.3 94.2 90.6 92.1 90.9 Glyoxal yield% 91.8 90.6 91.2 90.5 93.2 73.0 88.5 90.0

[0072] Data processing: Ethylene glycol conversion rate % = (ethylene glycol in the raw material - ethylene glycol in the product) / ethylene glycol in the raw material * 100%.

[0073] It can be seen from Table 1 that when the main catalyst is copper, the co-catalyst is zinc, and the carrier is alumina, both the ethylene glycol conversion rate and the glyoxal selectivity have better effects.

[0074] From Table 2, it can be seen that in Comparative Example 1, the carrier is directly put into the reaction solution for adsorption, and ethylene glycol has a conversion rate, but the selectivity of glyoxal is slightly low, which may be due to the main and auxiliary catalysts being mainly adsorbed on the surface of the carrier pores, resulting in too many active sites, resulting in too fast reaction and increased side reactions. In Comparative Example 4, due to the excessive concentration of the catalyst aqueous solution, although the specific surface area of ​​the catalyst still meets the requirements, the selectivity of glyoxal is reduced, and the reason may be that the solution concentration is too high, resulting in the main and auxiliary catalysts on the carrier aggregation phenomenon, resulting in strong local activity, resulting in increased side reactions. In Comparative Example 5, during the precipitation reaction, the temperature was maintained at 100 ° C, resulting in an increase in specific surface area, a decrease in the wall thickness of the pores in the carrier, an increase in the exposed main and auxiliary catalysts, resulting in an accelerated reaction speed, an increase in side reactions, and a reduction in the yield of glyoxal. In Comparative Example 6, due to the high calcination temperature, the carrier volume shrinks, the pores shrink, and the ethylene glycol conversion rate decreases. In Comparative Example 7, the calcination temperature was too low, and although the specific surface area of ​​the carrier met the requirements, the acidity of the carrier was enhanced, resulting in an increase in side reactions. In Comparative Example 8, the calcination time was too long, and although the specific surface area of ​​the carrier met the requirements, and during the reaction, ethylene glycol had a high conversion rate, the selectivity of glyoxal was reduced. The reason may be that the calcination time was too long, causing some of the main and auxiliary catalysts in the carrier to diffuse and aggregate outward, increasing the active sites and increasing the side reactions.

Claims

1. A catalyst for dehydrogenating ethylene glycol to produce glyoxal, characterized in that: The composition comprises the following components in weight ratio: 45-55% of main catalyst, 25-35% of co-catalyst, 10-30% of carrier; wherein: The main catalyst is at least one metal or its oxide selected from IB and VIII; The promoter is at least one metal selected from IIB and VIB or its oxide; The carrier is at least one of aluminum oxide and silicon oxide; When calculating the ratio of the main catalyst to the co-catalyst, both are converted into metal elements; Before using the catalyst, the catalyst is first reduced to reduce the oxides contained in the main catalyst and the co-catalyst to metal elements.

2. The catalyst according to claim 1, characterized in that The main catalyst is at least one of copper, copper oxide, iron and iron oxide; The promoter is at least one of zinc, zinc oxide, cadmium, cadmium oxide, molybdenum and molybdenum oxide.

3. The catalyst according to claim 1, characterized in that Prepared by the following steps: (1) Prepare the soluble salts of the main catalyst and the co-catalyst into an aqueous solution, stir evenly, and then add the carrier precursor to the aqueous solution to form a reaction solution: (2) maintaining stirring, heating the reaction solution to a set temperature, adding an alkaline precipitant, performing a precipitation reaction, aging, and then filtering to obtain a filtrate; (3) The filtered material is dried, calcined, and pressed into tablets to form a product.

4. The catalyst according to claim 3, characterized in that In the aqueous solution, the mass percentage of the soluble salt of the main catalyst is 5-16%, and the mass percentage of the soluble salt of the co-catalyst is 4-8%.

5. The catalyst according to claim 3, characterized in that In step (2), the precipitation temperature is 50-90° C., the pH value during the precipitation reaction is 8-11, and the aging time is 2-12 h.

6. The catalyst according to claim 3, characterized in that In step (3), the drying temperature is 90-150° C., and the drying time is 0.5-5 h; the roasting temperature is 500-600° C., and the roasting time is 3-5 h.

7. Use of the catalyst according to any one of claims 1 to 6 in the dehydrogenation of ethylene glycol to produce glyoxal.

8. The use according to claim 7, characterized in that: The catalyst is crushed into 20-40 mesh particles and loaded into the reactor, and the catalyst is reduced at a pressure of 1.8-2.2Mpa and a temperature of 200℃-300℃; then ethylene glycol is introduced into the reactor for dehydrogenation reaction; during the dehydrogenation reaction, the reaction pressure is normal pressure, the reaction temperature is 350-380℃, and the mass space velocity is 0.1-0.4h -1 .

9. The use according to claim 8, characterized in that: The reactor is a fixed bed reactor.

Citation Information

Patent Citations

  • Copper-carried crystallization silver catalyst for gas-phase oxidation synthesization of biformyl and its preparing method

    CN101024183B

  • Preparation process of glyoxal

    CN109678683A